STRATEGI DAKWAH PADA MASYARAKAT TAREKAT (STUDI KASUS PADA KEGIATAN TAREKAT QODIRIYAH WA NAQSYABANDIYAH DI PONPES FUTUHIYYAH MRANGGEN DEMAK) - M. Rais Ribha Rifqi (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The aim of this paper is to find out the most effective strategy to conduct Da’wa in the setting of tarekat society. Tarekat Qadariyah wa Naqsabandiyah is used as a case to examine such strategy in practice. This paper argued that transformative Da’wa as a distinctive method of preaching Islam suit the needs and demands of the tarekat society. Most of the members of tarekat come mainly from rural areas where they already have their intensive Islamic education in Islamic boarding schools (Pondok Pesantren) thus the need for enrichment in terms of Islamic teachings is relatively low. However, this paper suggest that what these people need the most is capacity building in terms of economic and political skill since those skillsets areimportant for the success in life. By becoming successful in life in the world, the main objective of Tarekat Qadariyah wa Naqsabandiyah, which is to create balance between spiritual and practical life in this world, could be fulfilled.Keywords: Da’wa, transformative Da’wa, tarekat, Qadiriyah wa Naqsabandiyah.